Qual é o nível de alfabetismo em saúde bucal necessário para escolher e quantificar apropriadamente o dentifrício fluoretado para crianças? - Sara Oliveira Lisboa (2019)
Fluoride toothpaste are the major carriers for fluoride, and their proper use can help balance the de-remineralization process while keeping the risk of fluorosis low. The level of Oral Health Literacy (OHL) of parents interferes in the health outcomes of their children. This study aimed to evaluate the level of literacy required to select and apply the appropriate amount of fluoride toothpaste indicated for children. A total of 171 literate parents/caregivers of children aged 0 to 10 years-old who were attended at the HC-UFMG Children's in risk Outpatient Clinic, had Portuguese as their mother language and had not received guidance on the use of dentifrice participated in the study. OHL was measured using BREALD-30 (adequate 26-30) and the Brazilian version of OHL-AQ (adequate 14-17). The tasks that serve to categorize each skill level are those performed correctly by 75% of the people in that literacy level. Parents/caregivers received standardized guidelines on the amount of toothpaste to be dispensed at the toothbrush (0.03g) and ideal concentration of fluorine (1100 ppm). Then, they were asked to quantify a toothpaste in a children's toothbrush and to choose from four toothpastes for children (with different concentrations of fluoride) which were in accordance with the orientation received. The percentage of parents/caregivers with adequate OHL level measured withBREALD-30 was 34%, of these 45.8% matched the amount and 78% correctly chose the toothpaste. Using OHL-AQ, 30% of the parents/caregivers had an adequate level of OHL, of these 54.9% quantified and 70.6% chose the toothpaste correctly. There was an association between the OHL level measured by the OHL-AQ and the toothpaste quantification: the parents/caregivers who correctly quantified had higher OHL-AQ scores than those who did it wrong (p = 0.034, Mann Whitney test). Parents/caregivers with an adequate OHL level had difficulty dispensing the adequate amount, but correctly chose the toothpaste. The other parents did not demonstrate ability to perform either of the tasks. There was no association between the performance of the parents/ guardians in the quantification and the choice of the toothpaste with the socioeconomic and demographic variables nor with the ability to recognize words in the dental area.